Part II.: Dissimilar friction stir welding of nickel titanium shape memory alloy to stainless steel – microstructure, mechanical and corrosion behavior - Parker West (17268946) (2021)
In the present work, nickel-titanium (NiTi) shape memory alloys (SMAs) is joined to 304 stainless steel (SS) using friction stir welding (FSW) using process parameters of 400 rpm and a constant tool translation speed of 75 mm/min. The macrostructure of the dissimilar weld showed some surface tunneling defects but there were regions of the weld that were defect free and without evidence of intermetallics at the interface. The weld stir zone (SZ) showed grain refinement compared to both base materials (BM). NiTi side of the joint showed very fine thermomechanical affected zone (TMAZ) and absence of a distinct heat affected (HAZ) zone, resulting in very little variation in microhardness. SS side of the weld showed typical FSW microstructural zones with higher microhardness in the SZ (270 HV) compared to BM (185 HV). Tensile testing of the weld showed a small initial plateau region, characteristic of shape memory alloys (SMAs) arising from NiTi part of the weld. Importantly, the transformation temperatures of NiTi, measured by differential scanning calorimetry (DSC) from different weld zones, varied by no more than 4 °C. Corrosion properties of the weld zone investigated in 3.5 wt. % NaCl solution showed moderately inferior corrosion resistance of dissimilar weld, compared to individual base metals, as characterized by the surface film impedance and corrosion current density. The decreased corrosion resistance was attributed to inhomogeneous passive film formed across the weld due to zonal heterogeneities. The predicted and measured galvanic parameters of the galvanically coupled base metals suggested that there appeared to be negligible galvanic effects. The results from the study show that with further development, FSW can be successfully utilized to create dissimilar joints between NiTi and stainless steel. Other Information Published in: Journal of Advanced Joining Processes License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jajp.2021.100072